O-16 Lean body weight based dosing achieves comparable systemic pantoprazole exposures for normal-weight and overweight/obese children. Issue 10 (20th September 2017) - Shakhnovich,; Abdel-Rahman,; Friesen,; Pearce,; Gaedigk,; Weigel,; Leeder,; Kearns,
Abstract : Background: We previously reported increased AUCtot and decreased CL/F for the commonly prescribed pro-ton pump inhibitor (PPI) and CYP2C19 substrate, pan-toprazole, in obese vs. non-obese children. In light of increasing concerns regarding adverse events associated with high systemic exposure to PPIs in children (e.g., os-teopenia, infection, micronutrient deficiencies), we aimed to identify a pantoprazole dosing strategy appropriate for overweight/obese children, who are six times more likely to suffer from gastroesophageal reflux disease and require PPI therapy than normal weight peers. Given that most physiologic metabolic processes occur in lean body tissues, lean body weight (LBW) based doing was imple-mented in this prospective paediatric pharmacokinetic investigation. Methods: 62 children (6–17 years of age; 39% Female), genotyped for CYP2C19 *2, *3, *4, *17 alleles (TaqMan), re-ceived a single oral dose of pantoprazole (1.2 mg/kg lean body weight). LBW was calculated via the Janmahasatian equation. Plasma pantoprazole and metabolite concen-trations were measured (HPLC-UV) at 10 time-points, over 8 hours, and pharmacokinetic parameters (PK) generat-ed via non-compartmental techniques (Kinetica 5.0). For children with at least one wild-type CYP2C19 allele (*1), select pantoprazole PK were compared in normal-weight (Body Mass Index (BMI) 10-84th% for age; n=29) and over-weight/obese (BMI ≥85th% for age; n=30) children, using independent student t-test (SPSS v23; α=0.05). Results: No statistically significant differences were observed for pantoprazole AUCtot in normal-weight (13.9±32.2 µMolar*h) vs. overweight/obese (14.68±31.03 µMolar*h) children (p=0.9). No statistically significant dif-ferences in pantoprazole CL/F (23.9±16.6 vs. 19.8±25.8 L/h; p=0.5) or Cmax (5.66±3.8 vs. 7.76±4.4 uMolar; p=0.06) were observed between normal-weight and overweight/obese children. Conclusion: LBW, rather than total body weight, based dosing is most appropriate to achieve comparable sys-temic exposures to pantoprazole for normal-weight and overweight/obese children. This dosing strategy appears to eliminate the systemic pantoprazole overexposure previously observed in obese children and will likely min-imize their risk for adverse events associated with high-dose PPI therapy. Future pharmacokinetic-pharmacody-namic studies of PPIs may be warranted for overweight and obese children.